An introduction to the new testament - Carson, D. A.; Moo, Douglas J. (Grand Rapids, Michigan : Zondervan, 2005)
An Introduction to the New Testament focuses on "special introduction," that is, historical questions dealing with authorship, date, sources, purpose, audience, and so forth. This approach stands in contrast to recent texts that concentrate more on literary form, rhetorical criticism, and historical parallels--topics the authors don't minimize, but instead think are better given extended treatment in exegesis courses. By refocusing on the essentials, An Introduction to the New Testament ensures that the New Testament books will be accurately understood within their historical settings. For each New Testament document, the authors also provide a substantial summary of that book's content, discuss the book's theological contribution to the overall canon, and give an account of current studies on that book, including recent literary and social-science approaches to interpretation.
Thinking about the study of the New Testament -- The synoptic Gospels -- Matthew -- Mark -- Luke -- John -- Acts -- New Testament Letters -- Paul : apostle and theologian -- Romans -- 1 and 2 Corinthians -- Galatians -- Ephesians -- Philippians -- Colossians -- 1 and 2 Thessalonians -- The Pastoral Epistles -- Philemon -- Hebrews -- James -- 1 Peter -- 2 Peter -- 1, 2, 3 John -- Jude -- Revelation -- The New Testament canon.
Includes bibliographical references and index.
English.
Keywords: Bible N.T. -- Introductions